2014
DOI: 10.1088/0964-1726/23/6/065023
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pull-in instability of a micro-actuator made from nonlinear elasticity materials

Abstract: This paper investigates the dynamic pull-in instability of a micro-actuator made from nonlinear elasticity materials. The theoretical formulations are based on Bernoulli–Euler beam theory and include the effects of both material nonlinearity and mid-plane stretching due to large deformation. By employing the Galerkin method, the nonlinear partial differential governing equation is decoupled into a set of nonlinear ordinary differential equations which are then solved using the Runge–Kutta method. Numerical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Therefore, in this paper, this model, presented in equation (2), is going to be used in the first integrant in equation (1) to include the effects of material nonlinearity on the magneto-elastic behavior of the embedded nanobeams. The appropriateness of the model was proved experimentally [46] and applied already in computational studies [49][50][51][52].…”
Section: Mathematical Formulationmentioning
confidence: 94%
“…Therefore, in this paper, this model, presented in equation (2), is going to be used in the first integrant in equation (1) to include the effects of material nonlinearity on the magneto-elastic behavior of the embedded nanobeams. The appropriateness of the model was proved experimentally [46] and applied already in computational studies [49][50][51][52].…”
Section: Mathematical Formulationmentioning
confidence: 94%
“…On basis of the normal stress-strain constitutive relationships of nonlinear elasticity materials mentioned above, we had done some work to study their mechanical behavior and dynamics. By using a first and third powers function to fit the nonlinearly elastic normal stress-strain model of Al-1%Si (Florando and Nix, 2005), a typical case of nonlinear elasticity material, we had obtained the results of some work such as a nonlinear dynamic analysis (Peng et al, 2014b) and the dynamic pull-in instability (Peng et al, 2014a) of micro-actuators and nonlinear electrodynamic analysis (Peng et al, 2017) and nonlinear free vibration (Lin et al, 2021) of sizedependent microbeams, where the studied structures were made of Al-1%Si. The obtained results showed that the effect of nonlinear elasticity was important, in other words, nonlinearly elastic normal stress-strain constitutive relationships softened bending stiffness and lateral vibration frequencies compared with approximatelysimplified linear ones.…”
Section: Mmms 184mentioning
confidence: 99%
“…By using a first and third powers function to fit the nonlinearly elastic normal stress-strain model of Al-1%Si (Florando and Nix, 2005), a typical case of nonlinear elasticity material, we had obtained the results of some work such as a nonlinear dynamic analysis (Peng et al. , 2014b) and the dynamic pull-in instability (Peng et al. , 2014a) of micro-actuators and nonlinear electro-dynamic analysis (Peng et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, because the elastic moduli of NcMs are likely to decrease due of the interface effect, the material structure can affect the rigidity through a softening mechanism depending on the grain size. Therefore, the classical mathematical models [17,[55][56][57] lose the accuracy to estimate the pull-in voltage values of actuated beams. Moreover, including only couple stress effect in the mathematical model [32,33,34] results in an overestimation of the pull-in voltage values of actuated beams.…”
Section: Materials Structure and Couple Stress Effects On The Static Dmentioning
confidence: 99%